Oral History Program Interview: Robert Dinwiddie - Dinwiddie, Robert
DinWiddie was born in Wylie, Collin County, Texas on February 7, 1896. He and his family would make the trip to Tulare, California where he was involved with constructing the Linnell Camp among others. His interview includes information regarding strikes and their violence, labor abuses, the WPA and different forms of welfare, hostilities toward "Okies," and that The Grapes of Wrath was very accurate.